Moving Biofortified Cassava Products Closer to Market in Nigeria - Oteh, Ogbonnaya Ukeh; Hefferon, Kathleen; Agwu, Nnanna Mba (Frontiers in Sustainable Food Systems, 2020)
Food must be acceptable, affordable, and available to consumers and consumers must have the resources, knowledge, and correct mindset to purchase and consume these foods. The narrative of this study centered on moving biofortified food closer to market by looking at awareness, adoption, and consumer mindsets as pillars to achieve market access. Our findings show that in Abia state, Nigeria, consumers are aware of biofortified cassava. This signifies a high market potential and economic opportunity for stakeholders in the supply chain. Unfortunately, consumers lack understanding of biofortified cassava's nutrition value. The high adoption level of biofortified cassava has implications on investment and stimulation of the local economy. The study identified accessibility, purposefulness and innovation as vital mindset drivers to scale market demand, and factors that affect both consumption, production, and marketing of the product. This study provides insight regarding potential priority areas of action for government policy interventions to stimulate demand and supply opportunities. This study also provides evidence that scaling up demand will depend on awareness creation. There is a need to improve communication networks to provide overwhelming product acceptance, adoption, and consumption of biofortified cassava. This will help change remaining myths about agro-biotechnology and the bioeconomy.